Implementasi Transaction Processing System dan Decision Support System dalam Pengambilan Keputusan Berbasis Web (Studi Kasus: Toko Lion) - Cessy, Cessy; Budi, Akhmad (Jurnal Informatika dan Bisnis, 2025)
The human need for consumer goods continues to increase, requiring grocery stores to operate efficiently. However, many stores still rely on manual record keeping which hinders real-time data access and increases the risk of recording errors. This research implements a web-based Transaction Processing System (TPS) and Decision Support System (DSS) to improve the operational efficiency of Toko Lion. By using qualitative and quantitative research methods through interviews, observations, and literature studies, this research analyzes the comparison between manual systems and web-based systems. The results showed that the system developed was able to increase the speed of recording transactions, the accuracy of stock data, and the presentation of more systematic financial reports. This implementation is proven to improve the efficiency of grocery store management and can be a reference for other small businesses in adopting digital technology.